2016
DOI: 10.3174/ajnr.a4699
|View full text |Cite
|
Sign up to set email alerts
|

Current Trends and Results of Endovascular Treatment of Unruptured Intracranial Aneurysms at a Single Institution in the Flow-Diverter Era

Abstract: BACKGROUND AND PURPOSE:During the past several years, the number of unruptured aneurysms treated with endovascular techniques has increased. Traditionally, coil embolization was the treatment of choice for these lesions; however, recently flow diversion has become a viable, and in some cases superior, treatment option. The current single-center study presents results and trends of endovascular treatment with flow diversion and coil embolization in an unselected group of patients with unruptured intracranial an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…With the development of flow-diverting stents, such as the Pipeline embolization device (PED), many of these aneurysms can now be treated endovascularly. 8,24 Estimates suggest that nearly 50% of all aneurysms can be treated with flow diversion-a statistic that highly varies based on aneurysm location within the cerebral circulation. 7 Despite FDA approval of the PED in 2011, there is no corresponding inflection point in trends of bypass utilization.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of flow-diverting stents, such as the Pipeline embolization device (PED), many of these aneurysms can now be treated endovascularly. 8,24 Estimates suggest that nearly 50% of all aneurysms can be treated with flow diversion-a statistic that highly varies based on aneurysm location within the cerebral circulation. 7 Despite FDA approval of the PED in 2011, there is no corresponding inflection point in trends of bypass utilization.…”
Section: Discussionmentioning
confidence: 99%
“…With the expansion of FDS use beyond the large and giant wide-necked aneurysms of the ICA not amenable to coil em-bolization, a comparison can now be made between traditional coil embolization and FDS for treatment of cerebral aneurysms. Petr et al 91) reported their institutional series of endovascular treatment of 310 patients with aneurysms of varied size and locations. Treatment modalities included both coil embolization and FDS.…”
Section: Coil Embolization Vs Fdsmentioning
confidence: 99%
“…FDs are a reconstructive treatment in which altered flow within an aneurysm induces gradual remodeling and eventual thrombosis of the aneurysm. Several studies have demonstrated good safety and efficacy of FDs for the treatment of unruptured intracranial aneurysms, [8][9][10][11][12][13][14][15][16][17] though the safe use of these devices requires the use of dual antiplatelet therapy. [18][19][20] Understandably, the need for antiplatelet medications and the delayed nature of aneurysm thrombosis have tempered en-thusiasm for using FDs for ruptured aneurysms.…”
mentioning
confidence: 99%